See Inside Pirate Ships - Jones, Rob Lloyd and Muhle, Jorg (London Usborne, 2007)
Caribbean pirates tend their ship, attack a merchant vessel, and sail to a haven; Chinese pirates attack and are defeated by the Royal Navy; and divers explore sunken ships, with illustrations that readers can flip open for further details. On board pages.
Include Color Illustrations
Keywords: Pirates -- Lift-the-flap books -- Ships